Social Equipment Square on the Waterfront: Study for the Cocaia Urban River Port - Junior, Moacir Zancopé; Delijaicov , Alexandre (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – This study investigates São Paulo’s historical relationship with its water bodies, analyzing public architecture and urban infrastructures for environmental sanitation, mobility, and river transportation. The focus is on Porto Cocaia, at the Billings Reservoir, considering its topography, history of urbanization, and potential integration with public transportation and urban services. Methodology – The research adopts architectural design as an investigative method, exploring concepts of place, program, and construction. It is based on contributions from the Grupo Metrópole Fluvial (GMF) and studies developed at LABPROJ-FAU-USP. The analysis includes topographic, historical, and urban planning surveys, as well as the development of diagrams, implantation studies, sections, and physical models to assess the architectural proposal. Originality/relevance – The study fills a gap by integrating public architecture and urban infrastructure within a metropolitan water context. The research highlights Porto Cocaia as a strategic hub for sustainable mobility and the requalification of the relationship between the city and its water bodies, fostering new perspectives on urban planning and occupation. Results – The research proposes the implementation of a public facilities square, including a dock, bus terminal, ferry station, environmental education center, and a farmers’ market. The project ensures integration between these elements and the urban landscape, respecting the site’s topographical variations and optimizing multimodal mobility. Theoretical/methodological contributions – The study reinforces the use of architectural design as a tool for academic and urban research. The proposal is based on an integrated analysis of public space and infrastructure, contributing to discussions on the occupation of São Paulo’s riverbanks. Social and environmental contributions – The research emphasizes the requalification of riverside areas as a strategy to enhance accessibility, promote sustainable mobility, and expand public services. The integration between river transport and urban facilities strengthens the city-water connection, generating positive environmental and social impacts.